Anti -inflammatory and Acute Toxicity Effects of Pittosporum tetraspermum Wight and Arn. on Rats - S. Ignacimuthu2, P.J. Rosakutty1, A. Stella Roslin1* and (Journal of Phytology, 2010)
<div style="border-right: medium none; border-top: windowtext 1pt solid; background: white; border-left: medium none; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt; padding: 0in;"> Abstract The anti-inflammatory effect of Pittosporum tetraspermum was studied in carrageenan – induced oedema in albino rats. Among the plant parts tested the methanol extract of root bark and stem bark exhitbited significant (P<0.01) oedema suppressant activity. The potency of the extract of root bark was superior to the reference drug phenylbutazone. The result suggests that the bark of P. tetraspermum has potential anti-inflammatory activity that supports its use in folk-therapy for inflammatory disorders. The acute toxicity study proved that the crude extract of the bark was non-toxic up to 2g/kg per oral (p.o.). Key words: Anti-inflammatory, Carrageenan, Acute-toxicity, Induced oedema <span style="font-weight: normal; font-size: 7pt; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">P.J. Rosakutty et al. Anti -inflammatory and Acute Toxicity Effects of Pittosporum tetraspermum Wight and Arn. on Rats. <span style="font-weight: normal; font-size: 7pt; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">J Phytol 2/6 (2010) 14-20